Spectrophotometric determination of urinary iodine by the Sandell-Kolthoff reaction subsequent to dry alkaline ashing. Results from the Czech Republic in the period 1994-2002 - Bílek, Radovan; Bednár, Jirí; Zamrazil, Václav (Clinical chemistry and laboratory medicine, 2005)
The Czech Republic is an iodine-deficient area. Insufficient iodine intake was reduced by enriching cooking salt with iodine in the range 20-34 mg I/kg. An important indicator for tracking changes in iodine nutrition over time is accurate information about urinary iodine concentrations in the population. In this paper we describe and characterize our method used for the determination of iodine in biological material, which is based on alkaline ashing of urine specimens preceding Sandell-Kolthoff reaction using brucine as a colorimetric marker. The losses of radioiodine added during sample preparation have not exceeded 0.001%. The detection limit is 2.6 microg I/L and the limit of quantification is 11.7 microg I/L, with intra-assay precision of 4% and inter-assay precision of 4.9%. During the period 1994-2002, the urinary iodine concentration was determined in 29,612 samples in the Institute of Endocrinology. The mean basal urinary iodine concentrations+/-SD were 115+/-69 microg I/L. Of the samples, 0.7% were in severe (<20 microg I/L), 9.6% in moderate (20-49 microg I/L), 40.1% in mild (50-99 microg I/L), 35.6% in adequate (100-200 microg I/L), and 14.0% in more than adequate (>200 microg I/L) subsets of iodine nutrition. A statistically significant (p<0.00001) difference was found between mean male (127 microg I/L) and female (112 microg I/L) urinary iodine, and an inversely proportional trend also exists in the age-related data.
Keywords: senioři; Reproducibility of Results; senioři nad 80 let; reprodukovatelnost výsledků; kojenec; mladiství; Česká republika; sexuální faktory; Middle Aged; jod; mužské pohlaví; Infant; Adult; Czech Republic; dítě; kolorimetrie; Child; věkové faktory; spektrální analýza; Aged, 80 and over; Child, Preschool; Infant, Newborn; ženské pohlaví; novorozenec; Humans; předškolní dítě; Colorimetry; Sex Factors; lidé středního věku; Iodine; Age Factors; Spectrum Analysis; dospělí; Female; Aged; Adolescent; lidé; Male